Productivity premia for German manufacturing firms exporting to the Euro-area and beyond: First evidence from robust fixed effects estimations - Vincenzo Verardi; Joachim Wagner (Institute for the Study of Labor (IZA), 2010)
This paper makes three contributions. (1) It summarizes in tabular form a recent literature made of 36 micro-econometric studies for 16 different countries on the relationship between export destination and firm performance. (2) It reports estimates of the productivity premium of German firms exporting to the Euro-zone and beyond, controlling for unobserved time invariant firm specific effects, and tests for self-selection of more productive firms into exporting beyond the Euro-zone. (3) It corrects a serious flaw in hitherto published studies that ignore the potentially disastrous consequences of extreme observations, or outliers. The paper shows that estimates of the exporter productivity premium by destination are driven by a small share of outliers. Using a clean sample without outliers the estimated productivity premium of firms that export to the Euro-zone only is no longer much smaller that the premium of firms that export beyond the Euro-zone, too, and the premium itself over firms that serve the German market only is tiny. Furthermore, an ex-ante differential that is statistically significant and large only shows up for enterprises that exported to the Euro-zone already and start to export to countries outside the Euro-zone. These conclusions differ considerably from those based on non-robust standard regression analyses.
Keywords: F14; C23; C81; C87; 330; Robust estimation; panel data; exporter productivity premium; export destinations; Exportindustrie; Auslandsmarkt; Produktivität; Unternehmensentwicklung; Schätzung; Deutschland; Eurozone